Students’ Critical Thinking Skills in Innovating Problem Solving in the Physics Entrepreneurship Course - Gunarjo S Budi; Fenno Farcis (Berkala Ilmiah Pendidikan Fisika, 2021)
The 21st century physics educators are expected to have 21st century skills, one of which is having life and career skills. One of the life skills assets is professional entrepreneurship. This study aimed to 1) determine the profile of students' critical thinking skills in innovating problem-solving during physics entrepreneurship course and 2) determine students’ responses about critical thinking skills in innovating problem solving.  This research conducted using preliminary research methods with data collection techniques in the form of description test instrument that filled out by students, and student questionnaires instrument. The data obtained were analyzed descriptively qualitatively.  The study was conducted on 30 students of department of physics education at a university in the city of Palangkaraya.  The results showed that all aspects of critical thinking skills (Facione's version) that were measured, namely the ability to interpret, analyze, evaluate, inference, explain, and self-regulation were on average in the low category (56.9%).   Students gave agreed (A) to very agreed (VA) responses to the implementation of learning that applied critical thinking skills in innovating to solve problems. These results can be concluded that the students have very limited critical thinking skills in solving entrepreneurial problems, so that efforts are needed to improve students' critical thinking skills in solving entrepreneurial problems, one of which is by developing a learning model that can be applied to physics entrepreneurship course which hopefully can improve critical thinking skills of physics education students.